1991
DOI: 10.1002/jlb.50.4.364
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Alveolar and Pulmonary Intravascular Macrophages: Comparison of Immune Functions

Abstract: Although a substantial amount of information is available on pulmonary alveolar macrophages (PAMs), little is known about pulmonary intravascular macrophages (PIMs), a separate population of lung macrophages found apposed to the endothelium of pulmonary capillaries. We compared these two populations of lung immunocytes to determine their relative immunological activity. Our results suggest that PAMs are more phagocytic than PIMs; however, PIMs may be more efficient at lysing ingested bacteria than PAMs. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 39 publications
3
71
0
Order By: Relevance
“…However, it is possible that a larger sample size may have resulted in a significant response in diastolic and systolic pressures. Although the vasoactive mediators secreted by the equine PIMs remain unknown, it is possible that as with porcine PIMs, these cells may produce arachidonic acid metabolites following the uptake of the LPS [7,8]. Therefore, PIM depletion will eliminate a vascular source of pro-inflammatory vasoactive substances to reduce LPSinduced pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that a larger sample size may have resulted in a significant response in diastolic and systolic pressures. Although the vasoactive mediators secreted by the equine PIMs remain unknown, it is possible that as with porcine PIMs, these cells may produce arachidonic acid metabolites following the uptake of the LPS [7,8]. Therefore, PIM depletion will eliminate a vascular source of pro-inflammatory vasoactive substances to reduce LPSinduced pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This hypertensive response, however, is abolished following removal of PIMs [27]. In vitro evidence shows that porcine PIMs can metabolise arachidonic acid [7,8]. We have recently shown that bovine PIMs contain TNF-α and their depletion significantly inhibits the accumulation of inflammatory cells and pathology in acute lung disease in calves [26].…”
Section: Introductionmentioning
confidence: 96%
“…In the lungs, macrophages occur in the airways, alveolar spaces, interstitium, and microvessels. Pulmonary intravascular macrophages (PIMs) were recently identified as resident mononuclear phagocytes in cattle, sheep, goats, pigs and horses [4,5,7,29,35]. PIMs differentiate from monocytes in post-natal life and form firm adhesions with the capillary endothelium [15,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal lambs that do not have PIMs show diminished pulmonary vascular response to tracers compared with four-week old lambs that have PIMs [15]. Blecha et al showed that porcine PIMs secrete thromboxane and are cytolytic [7,8]. They also reported that the immunological characteristics of PIMs are similar to those of alveolar macrophages [8].…”
Section: Introductionmentioning
confidence: 99%
“…Miyamoto et al (15) reported a similarly restricted localization of inert microspheres in sheep lungs. PIM in vitro are phagocytic, although less so than alveolar macrophages (16), and generate substantial amounts of eicosanoids, including those incriminated in GBS-induced pulmonary hypertension, as well as various cytokines (16,17). Collectively, these findings support the view that PIM play a major role in clearance of CBS as it transits the pulmonary vascular bed and that clearance of the bacteria is important for release of mediators that incite the hypertensive response and attract additional inflammatory cells (e.g.…”
Section: Tx In Gbs-induced Plllmonary Hypertension As Shown Inmentioning
confidence: 99%